Shortening Anesthesia Duration does not Affect Severity of Withdrawal Syndrome in Patients Undergoing Ultra Rapid Opioid Detoxification - Shoaleh Shami; Karim Nasseri; Behzad Ahsan; Fariba Farhadifar (Acta Medica Iranica, 2010)
Ultra rapid opioid detoxification (UROD) is one of the new methods of detoxification. This method of detoxification involves putting patients under general anesthesia and actively giving them opioid antagonists. The objective of this study was to evaluate effects of anesthesia duration in UROD on severity of withdrawal syndrome. Sixty addicted patients seeking UROD procedure assigned randomly to one of the 2hr, 4hr or 6hr anesthesia duration groups. Premedication and anesthesia procedure (induction and maintenance) were the same for three groups. Detoxification was done for all patients with 50 mg oral naltroxane (prior to induction) and 20 mg intravenous naloxane (8 mg/bolus and 12 mg/infusion). Blood pressure, heart rate and respiratory rate were automatically measured and recorded every 5 minutes. The severity of withdrawal syndrome was measured and recorded every one hour during anesthesia, 2hours post-anesthesia, and 12 and 24 hours following the induction of anesthesia according to the Wang Scale modified by Lomier (WSMBL). Patients aged 20-58 in three groups. Three cases experienced delirium after detoxification that lasted 24 hours in one. Severity of withdrawal syndrome in patients of groups 2, 4 and 6 hour were 8.7, 7.4 and 5.1 respectively during anesthesia and 12.3, 11.1 and 13.9 after 18 hours of anesthesia. Results of this study showed that, in standard settings, UROD is a safe method for detoxification and has low complications. The withdrawal symptoms during and after anesthesia are low. Shortening the duration of anesthesia has no affect on severity of withdrawal syndrome during and after anesthesia.